Determinants of public golf course visitation and willingness to pay for turfgrass enhancement: A case study from Oklahoma, USA. (20th December 2018) - Joshi, Omkar; Fontanier, Charles; Harris, Dustin K.; Poudyal, Neelam C.; Kharel, Gehendra
Abstract: With increasing competition and rising operational costs, golf course managers are focusing on innovative approaches that can help attract and retain visitors. Therefore, understanding economic rationale for landscape improvement can help managers to prioritize operational budget. The purpose of this study was to identify the determinants of golfers' repeated visitation to public golf courses and understand economic rationale for aesthetic quality improvement in public golf facilities. We surveyed golf course visitors at Lakeside Memorial Golf Course, a municipal facility in Stillwater, Oklahoma. Study results suggest that golfers' frequency to revisit was positively influenced by prestige of the facility and course design. The willingness to pay (WTP) estimates, which accounted for respondent's maximum propensity to pay above already paid green fees, for winter turfgrass enhancements were about two times higher than their estimated costs. Study results suggested landscape improvement strategies and provided several recommendations to golf course management. Highlights: Golf courses have witnessed financial problems due to higher operational expenses. Prestige of the facility, course design, and golfer age increased visitation. Results suggested that turfgrass enhancement could be a justifiable investment.